2022
DOI: 10.1021/acs.joc.2c00587
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition of Hydantoin Derivatives Enabled by Tetraaza Macrocyclic Chiral Solvating Agents Using 1H NMR Spectroscopy

Abstract: Enantiomers of a series of hydantoin derivatives were prepared from d- and l-amino acids with p-tolyl isocyanate and 3,5-bis­(trifluoromethyl)­phenyl isocyanate as guests for chiral recognition by 1H NMR spectroscopy. Meanwhile, several tetraaza macrocyclic compounds were synthesized as chiral solvating agents from d-phenylalanine and (1S,2S)-(+)-1,2-diaminocyclohexane. An uncommon enantiomeric discrimination has been successfully established for hydantoin derivatives, representatives of five-membered N,N-hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Enhanced acidity of thiourea function compared to amide one, together with potentiality of 3,5-bis(trifluoromethyl)phenyl moiety as a booster of enantiodiscriminating capabilities, suggested [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 ] the possibility of changing the aromatic moiety of the CSA preparing thiourea derivatives 8a – b with exo–exo and exo–endo stereochemistry, respectively. Preliminarily, their efficiency was compared using amino acid derivatives with free carboxylic functionalities, on considering the possibility of introducing suitable probes as N -3,5-dinitrobenzoyl ( N -DNB), N-trifluoroacetyl ( N -TFA) and N -acetyl ( N -Ac) groups for the detection of enantiodifferentiation as in the cases of 9a – b , 10a , and 11a, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced acidity of thiourea function compared to amide one, together with potentiality of 3,5-bis(trifluoromethyl)phenyl moiety as a booster of enantiodiscriminating capabilities, suggested [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 ] the possibility of changing the aromatic moiety of the CSA preparing thiourea derivatives 8a – b with exo–exo and exo–endo stereochemistry, respectively. Preliminarily, their efficiency was compared using amino acid derivatives with free carboxylic functionalities, on considering the possibility of introducing suitable probes as N -3,5-dinitrobenzoyl ( N -DNB), N-trifluoroacetyl ( N -TFA) and N -acetyl ( N -Ac) groups for the detection of enantiodifferentiation as in the cases of 9a – b , 10a , and 11a, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Chiral amides [ 24 , 25 , 26 , 27 , 28 , 29 ] and especially chiral arylthioureas [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] are known to exhibit excellent enantiodiscriminating capabilities when employed as CSAs for the NMR enantiodiscrimination of chiral carboxylic acids [ 30 , 31 , 32 , 33 , 34 , 35 ] and derivatives of amino acids [ 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…丁传凡团队 [34] 基于环糊 精与青霉胺对映体之间的非共价相互作用能力差异, 采 用光谱耦合技术(IM-MS)对 D-和 L-Pen 的快速分析与识 别进行详细考察. 基于含手性 NH 功能基的环状有机分 子, 其骨架结构收敛, 能有效调控环缘上的 NH 功能基 与客体分子作用的空间取向, 在针对生物分子或药用有 机小分子的选择性识别作用及作用机制研究方面是一 类具有重要研究价值的人工受体分子 [35][36][37] .…”
Section: 引言unclassified
“…The high medicinal potential of hydantoins provoked intensive studies on the development of efficient methods for their diversity- and complexity-oriented assembly . With respect to 3,5-substituted hydantoins, the catalytic approaches to them are still limited . In 2013, Miao and coauthors reported an I 2 -mediated one-pot synthesis of azetidines using amino malonate derivatives and enones as reaction partners, in which they conducted the addition of ureidomalonate to chalcone for the stereoselective synthesis of the 3,5,5-trisubstituted hydantoin (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%